Fabrication and characterisation of graphene oxide saturable absorber for Q-Switched fiber laser generation / Ahmad Zarif bin Zulkifli - Zulkifli, Ahmad Zarif (2015)
Graphene oxide (GO) material is produced through chemical oxidation of graphite to produce large scale of graphene material by chemical reduction of GO. Its hydrophilic property and kinetically stable in colloidal suspensions allows new saturable absorber (SA) fabrication technique to be explored suited with the optical fiber technology where the graphene and carbon nanotube could not achieve due to their chemical properties limitation. In this regard, GO can be used as an alternative material to build SA device in generating Q-switched fiber laser. Such fiber laser can be used in various applications such as in range finding, remote sensing and so on that utilize high pulse energy and short pulse width. In this thesis, two different types of GOSA devices have been successfully fabricated and characterised for Q-switched fiber laser generation at the telecommunication C-band and eye-safe 2 micron band. The first GOSA device is fabricated from pure graphite using simplified’s Hummer’s method to produce 0.5 mg/mL GO colloidal suspension. Then a film form is yielded on a 90 mm petri dish through drop-casting method. Raman spectrum analysis on the defect density of the film via the intensity ratio value (ID/IG) reveals that the fabricated GO has high degree of crystalline defect and some partially retain aromatic sp2 carbon ring structure which is mainly responsible for saturable absorption. The Q-switched fiber laser at C-band, has a Q-switched threshold of 65 mW with a maximum average output power of 0.11 mW, and pulse energy of 4.3 nJ. The narrowest pulse width of 7.7 μs and a maximum repetition rate of 27.2 kHz are obtained at the maximum pump power. The second GOSA device is fabricated via optical deposition method by having graphite oxide nanopowder dispersed in water-contained beaker and deposited on a fiber ferrule facet. A comparison analysis on the intensity ratio (ID/IG) and effective aromatic cluster correlation length, LAeff suggests that GOSA by optical deposition (ID/IG=0.92) has higher capacity for saturable absorption than the GOSA film (ID/IG=0.86) due to having larger effective aromatic cluster size and more aromatic rings. The Q-switched fiber laser at 2 micron region using the optically deposited GO layers has a threshold of 125 mW with a maximum pulse repetition rate of 16.0 kHz and minimum pulse width of 9.8 μs. The maximum average output power of 0.3 mW and pulse energy of 18.8 nJ were obtained. In the third system, a commercial GO in a paper form has been compared with the GO film to evaluate the structure issue of the film that leads to nonsaturable loss. The GO paper has been successfully been utilized to generate narrow spacing Qswitched dual-wavelength fiber laser at the C-band region which will find useful for terahertz signal generation. This research work in generating Q-switched fiber lasers using the GOSAs have shown some potential where further system optimization is required to find their practical applications. Moreover, the advantages of GO properties has proven to provide an efficient solution that reduce time and cost to fabricate the saturable devices.